Salmon Gravlax Biopreservation With Lactic Acid Bacteria: A Polyphasic Approach to Assessing the Impact on Organoleptic Properties, Microbial Ecosystem and Volatilome Composition - Wiernasz, Norman; Leroi, Françoise; Chevalier, Frédérique; Cornet, Josiane; Cardinal, Mireille; Rohloff, Jens; Passerini, Delphine; Skırnisdóttir, Sigurlaug; Pilet, Marie-France (Frontiers in Microbiology, 2020)
Seafood and fishery products are very perishable commodities with short shelf-lives owing to rapid deterioration of their organoleptic and microbiological quality. Microbial growth and activity are responsible for up to 25% of food losses in the fishery industry. In this context and to meet consumer demand for minimally processed food, developing mild preservation technologies such as biopreservation represents a major challenge. In this work, we studied the use of six lactic acid bacteria (LAB), previously selected for their properties as bioprotective agents, for salmon dill gravlax biopreservation. Naturally contaminated salmon dill gravlax slices, with a commercial shelf-life of 21 days, were purchased from a French industrial company and inoculated by spraying with the protective cultures (PCs) to reach an initial concentration of 106 log CFU/g. PC impact on gravlax microbial ecosystem (cultural and acultural methods), sensory properties (sensory profiling test), biochemical parameters (pH, TMA, TVBN, biogenic amines) and volatilome was followed for 25 days of storage at 8°C in vacuum packaging. PC antimicrobial activity was also assessed in situ against Listeria monocytogenes. This polyphasic approach underlined two scenarios depending on the protective strain. Carnobacterium maltaromaticum SF1944, Lactococcus piscium EU2229 and Leuconostoc gelidum EU2249, were very competitive in the product, dominated the microbial ecosystem, and displayed antimicrobial activity against the spoilage microbiota and L. monocytogenes. The strains also expressed their own sensory and volatilome signatures. However, of these three strains, C. maltaromaticum SF1944 did not induce strong spoilage and was the most efficient for L. monocytogenes growth control. By contrast, Vagococcus fluvialis CD264, Carnobacterium inhibens MIP2551 and Aerococcus viridans SF1044 were not competitive, did not express strong antimicrobial activity and produced only few organic volatile compounds (VOCs). However, V. fluvialis CD264 was the only strain to extend the sensory quality, even beyond 25 days. This study shows that C. maltaromaticum SF1944 and V. fluvialis CD264 both have a promising potential as bioprotective cultures to ensure salmon gravlax microbial safety and sensorial quality, respectively.